Desensitization strategy for hypersensitivity reactions to carboplatin in five patients with gynecological cancer. Issue 11 (23rd August 2020) - Toyohara, Yusuke; Sone, Kenbun; Nishida, Haruka; Taguchi, Ayumi; Miyamoto, Yuichiro; Tanikawa, Michihiro; Mori, Mayuyo; Tsuruga, Tetsushi; Matsumoto, Yoko; Oda, Katsutoshi; Osuga, Yutaka; Fujii, Tomoyuki
Abstract: Aim: Carboplatin is a key drug for gynecologic cancers. However, hypersensitivity reactions (HSR) are major adverse effects that might necessitate carboplatin discontinuation. Desensitization is an effective method in patients who developed initial HSR and further required carboplatin treatment. Here, we aimed to evaluate our experience with the use of the carboplatin desensitization protocol in five patients at the University of Tokyo Hospital. Methods: We established a four‐step, 5‐h desensitization protocol for our hospital. Observational and retrospective analyses were performed. Additionally, we have shared the patients' clinical information with the emergency department to ensure the safety of this protocol. Results: Five patients with recurrent gynecological cancer were treated using this protocol. Four of the five patients were treated effectively and 28 of 29 desensitization protocols were completed successfully. In one patient, we switched to olaparib successfully after two courses of our protocol. One patient who developed grade 4 HSR during initial carboplatin administration developed grade 2 HSR and we discontinued the protocol. Conclusion: The carboplatin desensitization protocol is very efficient. The outcome of our protocol was on a par with other protocols. To the best of our knowledge, this is the first study to indicate that switching to olaparib can be considered a suitable option in patients who develop HSR to carboplatin.